2011
DOI: 10.1111/j.1439-0531.2010.01586.x
|View full text |Cite
|
Sign up to set email alerts
|

Fertility Results after Vaginal Deposition of Frozen‐Thawed Buck Semen Diluted with Two Different Extenders Using One‐ or Two‐Step Procedures

Abstract: In two field trials (T1 and T2), the effect of two different extenders for buck semen was tested. Semen from six (T1) and seven (T2) bucks of the Norwegian Dairy Goat breed was diluted either in a milk-based extender containing egg yolk (M) or in a commercially available extender without egg yolk [Andromed(®) (A)]. Dilution in M was performed in a two-step procedure including centrifugation of the ejaculates and removal of the supernatant, while dilution in A was performed in one step. During the two trials (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Moreover, [28] reported increase in spermatozoa mot ility in a co mmercial extender based on soybean in comparison with egg yolk -Tris based extender. Also, [29] revealed that there are no significant differences in fertilizat ion and conception rates between soybean extender (Andro med®) and egg yolk-milk based extender. There is no doubt that plant lecithin will substitute egg yolk and milk based extenders in near future due to the high performance of chilled and cryopreserv ed spermatozoa [30; 31; 32].…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, [28] reported increase in spermatozoa mot ility in a co mmercial extender based on soybean in comparison with egg yolk -Tris based extender. Also, [29] revealed that there are no significant differences in fertilizat ion and conception rates between soybean extender (Andro med®) and egg yolk-milk based extender. There is no doubt that plant lecithin will substitute egg yolk and milk based extenders in near future due to the high performance of chilled and cryopreserv ed spermatozoa [30; 31; 32].…”
Section: Resultsmentioning
confidence: 97%
“…However, it was found in this study that the quality of post-thawed spermatozoa quality after fumigation at 2 cm was higher, which contrasts with the findings of previous research. This difference may be attributed to variances in spermatozoa resistance to freezing, which could be influenced by species or breeds, as well as variances in the composition of the diluent used and the pre-equilibration time 32 , 33 . Another study on human spermatozoa have shown that differences in the volume of straws can also affect semen freezing 34 .…”
Section: Discussionmentioning
confidence: 99%
“…In goat, commercially acceptable pregnancy rates (67.5%) have been reported in case of cervical AI with cooled diluted fresh semen [1,13,31,32], whereas with F-T semen these figures are much lower [33][34][35]. In Thailand, in small holdings, prenancy rate of 29-30% have been reported when goats were artifically inseminated using F-T semen [36].…”
Section: Discussionmentioning
confidence: 99%